Intensive fruit culture in Kansas - Symns, Andrew B. (My University, 1898)
Introduction: The subject of fruit-culture in Kansas is an up to date question, and should be given due thought and careful consideration by every industrious and wide awake farmer. Not many years ago, it was considered impossible to raise fruit in the greater part of the state, but with the advancement of the westerner and the improvements in agriculture, the horticulturist has established his new ideas; and now, with the increased vegetation; larger rainfall, and better methods of conserving the moisture, together with the selection of varieties adapted to the local conditions, and improved methods of culture, many varieties of fruit can be successfully grown in nearly every country in the state. Kansas has already gained a reputation for her fruits and the time is not far distant when the great eastern markets will herald the Kansas fruits as they do now her several serials and livestock.
Citation: Symns, Andrew B. Intensive fruit culture in Kansas. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Livestock; Vegetation; Kansas; Horticulture; Farmers; Theses; Manuscripts (documents)